Long-term increase in secondary exposure to anticoagulant rodenticides in European polecats Mustela putorius in Great Britain. (May 2018) - Sainsbury, Katherine A.; Shore, Richard F.; Schofield, Henry; Croose, Elizabeth; Pereira, M. Gloria; Sleep, Darren; Kitchener, Andrew C.; Hantke, Georg; McDonald, Robbie A.
Abstract: As a result of legal protection and population recovery, European polecats ( Mustela putorius ) in Great Britain are expanding into areas associated with greater usage of second-generation anticoagulant rodenticides (SGARs). We analysed polecat livers collected from road casualties from 2013 to 2016 for residues of five SGARs. We related variation in residues to polecat traits and potential exposure pathways, by analysing stable isotopes of carbon (δ 13 C) and nitrogen (δ 15 N) in their whiskers. 54 of 68 (79%) polecats had detectable residues of at least one SGAR. Bromadiolone (71%) was the most frequently detected compound, followed by difenacoum (53%) and brodifacoum (35%). Applying historical limits of detection to allow comparison between these new data and previous assessments, we show that in the 25 years from 1992 to 2016 inclusive, the rate of detection of SGARs in polecats in Britain has increased by a factor of 1.7. The probability of SGAR detection was positively related to increasing values of δ 15 N, suggesting that polecats feeding at a higher trophic level were more likely to be exposed. Total concentrations of SGARs in polecats with detectable residues were higher in polecats collected in arable compared to pastoral habitats, and in the west compared to the east of Britain. The number of compounds detected and total concentrations of SGARs increased with polecat age. There was no evidence of regional or seasonal variation in the probability of detecting SGARs, suggesting that the current risk of exposure to SGARs does not vary seasonally and has increased (from that in the 1990s) throughout the polecat's range. We recommend quantification of current practices in rodenticide usage, particularly in the light of recent regulatory changes, to enable assessment and mitigation of the risks of secondary exposure to rodenticides in non-target wildlife. Graphical abstract: Image 1 Highlights: 79% of European polecats in England and Wales were exposed to rodenticides. 1.7-fold increase in detection of rodenticides in polecats since the 1990s. 71% polecats had residues of bromadiolone, 53% difenacoum, 35% brodifacoum. Enriched nitrogen isotope signatures were positively related to rodenticide detection. Liver rodenticide concentrations were higher in arable than pastoral habitats. Abstract : 79% of polecats in Great Britain were found to have been exposed to rodenticides from 2013 to 2016 and exposure has increased by a factor of 1.7 since the 1990s.